Using the PfEMP1 Head Structure Binding Motif to Deal a Blow at Severe Malaria (2014)
Plasmodium falciparum (Pf) malaria causes 200 million cases worldwide, 8 million being severe and complicated leading to similar to 1 million deaths and similar to 100,000 abortions annually. Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) has been implicated in cytoadherence and infected erythrocyte rosette formation, associated with cerebral malaria; chondroitin sulphate-A attachment and infected erythrocyte sequestration related to pregnancy-associated malaria and other severe forms of disease. An endothelial cell high activity binding peptide is described in several of this similar to 300 kDa hypervariable protein's domains displaying a conserved motif (GACxPxRRxxLC); it established H-bonds with other binding peptides to mediate red blood cell group A and chondroitin sulphate attachment. This motif (when properly modified) induced PfEMP1-specific strain-transcending, fully-protective immunity for the first time in experimental challenge in Aotus monkeys, opening the way forward for a long sought-after vaccine against severe malaria.